SISTEM PENDUKUNG KEPUTUSAN THE BEST MEDICAL EMPLOYEE BERBASIS WEB MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING(SAW) (STUDI KASUS : STARTUP KEI MEDIKA) - Puad, Lailyn; Limia Budiarti, Rike; Alfianto, Jefry (JURNAL AKADEMIKA, 2023)
Efficient assessment of medical employees is crucial for delivering quality healthcare services. This research proposes a Web-based Decision Support System (DSS) employing the Simple Additive Weighting (SAW) method to evaluate top employees and outstanding medical staff in the Kei Medika startup. The system assigns weights to evaluation criteria, generating rankings for employees. System evaluation results demonstrate efficiency and consistency in assessments. This technology aids in enhancing medical service quality by identifying high-performing staff.